DEVELOMPENT OF A VEHICLE SECURITY SYSTEM WITH LOCAL AND REMOTE CONTROL AND EVENT NOTIFICATIONS - Sánchez, Juan Manuel; Sogamoso Heredia, Omar; Villarreal López, Edwin (Redes de Ingeniería, 2013)
This article describes the development of a security monitoring device for vehicles which gives instant reports to the user about any anomaly that occurs in his absence. This device also allows remote and local control actions, using GSM technology and Bluetooth, giving more functionality than common vehicle security systems. In this paper the different development stages are presented, starting with a short review about existing relevant devices in order to identify the necessary functional requirements and innovation opportunities. Later, a block diagram of the device is presented and the specific design parameter are detailed. The final experimentation showed that the developed equipment has a greater functionality than existing devices and lower production cost.